What is a gospel? - Watson, Francis (William B. Eerdmans Publishing Company, 2022)
Machine generated contents note: Table of Contents1. What Is a Gospel? -- 2. Seven Ways to Dispose of Judas Iscariot -- 3. How Did Mark Survive? -- 4. Does Luke Need Q? -- 5. Q and the Logia: On the Discovery and Marginalizing of P.Oxy.1 -- 6. Luke Rewriting and Rewritten -- 7. The Gospel of the Apostles: The Epistula Apostolorum and the Johannine Tradition -- 8. Jesus versus the Lawgiver: Narratives of Apostasy and Conversion -- 9. Making Sense of the Betrayer: The Gospel of Judas and Its Predecessors -- 10. Reception as Corruption: Tertullian and Marcion in Quest of the True Gospel -- 11. Toward a Redaction-Critical Reading of the Diatessaron Gospel -- 12. Lindisfarne and the Gospels: The Art of Interpretation -- 13. Eschatology and the Twentieth Century: On the Reception of Schweitzer in English -- 14. A Reply to My Critics.